PENERAPAN MODEL PEMBELAJARAN PREDICT-OBSERVE EXPLAIN (POE) SEBAGAI SOLUSI ALTERNATIF UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA SISWA PADA MATERI HUKUM NEWTON KELAS X SMA - Nurhasana Nurhasana; Zuhdi Ma’aruf; Dedi Irawan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : Understanding is the level of ability expected by someone in understanding the meaning of the concept. Understanding the concept is a very important part in the learning process. The purpose of this study is to find out that the application of the predict-observe explain (poe) learning model can be an alternative solution to improve students' understanding of physics concepts. This study uses a quasi-experimental research method with a